2015
DOI: 10.1007/s11144-015-0840-5
|View full text |Cite
|
Sign up to set email alerts
|

Towards the mechanism of the oxidation of cyclohexylamine by molecular oxygen over alumina-based catalysts

Abstract: The oxidation of cyclohexylamine with molecular oxygen over a heterogeneous catalyst is an attractive one-step route to prepare a commercially important cyclohexanone oxime. The effect of the reaction conditions on the conversion of cyclohexylamine during its oxidation by molecular oxygen and on the selectivity of cyclohexanone and cyclohexanone oxime formation was investigated over heterogeneous catalysts (alumina and alumina supported silicotungstic acid). The present work is aimed at the enhancement of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The oxidants mainly consist of dioxygen, hydrogen peroxide, and a series of alkyl hydroperoxides. [7][8][9][10][11] Compared with other oxidants, dioxygen has obvious advantages regarding cost and safety. Therefore, dioxygen was used in most studies as the oxidant for the green oxidation of CHA.…”
Section: Introductionmentioning
confidence: 99%
“…The oxidants mainly consist of dioxygen, hydrogen peroxide, and a series of alkyl hydroperoxides. [7][8][9][10][11] Compared with other oxidants, dioxygen has obvious advantages regarding cost and safety. Therefore, dioxygen was used in most studies as the oxidant for the green oxidation of CHA.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 research of the activity of heterogeneous acid catalysts, and the selectivity to CHO was about 60.4% with 33.4% of CHA conversion employing alumina-supported silicotungstic acid. 12 Maldotti et al reported that the heteropoly acid ((nBu 4 N) 4 W 10 O 32 ) catalyst was effective in the acetonitrile solvent, but the conversion and selectivity have not been enhanced significantly. 13 Rakottyay et al proposed to use an organic amine-modified WO 3 /γ-Al 2 O 3 catalyst, and the selectivity to CHO reached 64%.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few decades, some notable research progress on the aerobic oxidation of CHA to CHO had been achieved. Early researchers were devoted to transition metal elements as active components for the synthesis of supported catalysts and had achieved good results. , Horváth et al focused on the research of the activity of heterogeneous acid catalysts, and the selectivity to CHO was about 60.4% with 33.4% of CHA conversion employing alumina-supported silicotungstic acid . Maldotti et al reported that the heteropoly acid ((nBu 4 N) 4 W 10 O 32 ) catalyst was effective in the acetonitrile solvent, but the conversion and selectivity have not been enhanced significantly .…”
Section: Introductionmentioning
confidence: 99%